Find a flight for me, Oscar! Motivational customer experiences with chatbots. - Jiménez-Barreto, Jano; Rubio, Natalia; Molinillo-Jiménez, Sebastián (Emerald, 2021)
Purpose. Drawing on the self-determination theory, the assemblage theory, and customer experience literature, we aim to develop a framework to understand motivational customer experiences with chatbots. Design/methodology/approach. We employ a multimethod approach to examine the interaction between individuals and airlines’ chatbots. Three components of self-determined interaction with the chatbot (competence, autonomy, and relatedness) and five components of the customer–chatbot experience (sensory, intellectual, affective, behavioral, and social) are analyzed qualitatively and quantitatively. Findings. The findings confirm the direct influence of self-determined interaction on customer experience and the direct effects of these two constructs on participants’ attitudes toward and satisfaction with the chatbot. The model also supports the mediating roles of customer experience and attitude toward the chatbot. Practical Implications. We offer managers a broad understanding of individuals’ interactions with chatbots through three elements: motivation to use chatbots, experiential responses, and individuals’ valuation of whether the interactions have amplified (or limited) the outcomes obtained from the experience. Originality/value. We contribute to the hospitality and tourism literature with a hybrid approach that reflects on current theoretical developments regarding human- and interaction-centric interpretations of customer experience with chatbots.
Keywords: Inteligencia artificial; Chatbot; Customer experience; Hybrid experiential model; Artificial intelligence